2009
DOI: 10.1002/met.164
|View full text |Cite
|
Sign up to set email alerts
|

Variability of extreme rainfall events over India during southwest monsoon season

Abstract: ABSTRACT:The spatial and temporal variability of extreme rainfall events over India and their long-term trend have been analysed during the southwest monsoon season from June to September (JJAS) by taking daily rainfall data for 55 years . The contribution of extreme rainfall events (Category iii with rainfall >124.4 mm day −1 ) to the total seasonal rainfall is also analysed for the same period. The analysis shows that the occurrence of extreme rainfall events over India during JJAS shows spatial variations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…Rainfall also shows an increase of about 1.3 mm/year in this period. Decreasing trends in Indian summer monsoon rainfall in last 50 years (Lau and Kim, 2010) and increasing number of extreme rainfall events (Goswami et al, 2006;Pattanaik and Rajeevan, 2010) have been repeatedly reported over this region in recent studies. Our analysis indicates that increasing CAPE over the Indian region may be responsible for increase in frequency of extreme events.…”
Section: Discussionmentioning
confidence: 68%
“…Rainfall also shows an increase of about 1.3 mm/year in this period. Decreasing trends in Indian summer monsoon rainfall in last 50 years (Lau and Kim, 2010) and increasing number of extreme rainfall events (Goswami et al, 2006;Pattanaik and Rajeevan, 2010) have been repeatedly reported over this region in recent studies. Our analysis indicates that increasing CAPE over the Indian region may be responsible for increase in frequency of extreme events.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, studies have found a rise in the summer monsoonal precipitation extremes over central India and northeastern Pakistan [15][16][17][18][19][20]. In contrast, precipitation extremes feature a falling trend over southwestern Pakistan [20], the eastern Gangetic plains and some parts of Uttaranchal, India [21].…”
Section: Introductionmentioning
confidence: 99%
“…The rainfall events were classified based on India Meteorological Department [ Table 1 of Pattanaik and Rajeevan (2010)]. The total number of rainy days were 109, 111 and 91, respectively, for 2014-2016, of which light rain (daily rainfall < 10 mm) constituted around 76% of total rainfall events.…”
Section: Wavelet Analysismentioning
confidence: 99%